High dose of epinephrine does not improve survival of children with out-of-hospital cardiac arrest: Results from the French National Cardiac Arrest Registry - Recher, Morgan; Canon, Valentine; Lockhart, Marguerite; Lafrance, Martin; Hubert, Hervé; Leteurtre, Stéphane (Frontiers in Pediatrics, 2022)
Objectives: The pediatric resuscitation guidelines recommend the use of 0.01 mg kg-1 epinephrine during a cardiac arrest; an epinephrine dose higher than that is not recommended. The first aim of this study was to determine the administration rate of high epinephrine dose during pediatric out-of-hospital cardiac arrest. The second aim was to compare the survival status in patients who received high or standard doses of epinephrine. Methods: This was a multicenter comparative post-hoc study conducted between January 2011 and July 2021 based on the French National Cardiac Arrest Registry data. All prepubescent (boys < 12 years old, girls < 10 years old) victims of an out-of-hospital cardiac arrest were included. To compare survival status and control bias, patients who received a high epinephrine dose were matched with those who received a standard epinephrine dose using propensity score matching. Results: The analysis included 755 patients; 400 (53%) received a high dose and 355 (47%) received a standard dose of epinephrine. The median dose (mg kg-1) per bolus was higher in the high-dose group than that in the standard dose group (0.04 versus 0.01 mg kg-1, P<0.001). Before matching, there was no between-group difference in the 30-day survival rate or survival status at hospital discharge. Matching yielded 288 pairs; there was no between-group difference in the 30-day survival rate or survival at hospital discharge (High dose, n=5; standard dose, n=12; Odds ratios: 2.40, 95% confidence interval: 0.85–6.81). Only 2 patients in the standard dose group had a good neurological outcome. Conclusions: More than 50% of the patients did not receive the recommended epinephrine dose during resuscitation. There was no association between patients receiving a high dose or standard dose of epinephrine with the 30-day survival or survival status at hospital discharge. Collaboration across multiple cardiac arrest registries is needed to study the application of pediatric guidelines.